2017
DOI: 10.3390/microorganisms5040069
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected High Diversity of Terrestrial Cyanobacteria from the Campus of the University of the Ryukyus, Okinawa, Japan

Abstract: Terrestrial cyanobacterial strains were isolated from the Nishihara campus of the University of the Ryukyus, Okinawa, Japan. The 13 sampling sites were distributed in a 200 m radius and appeared as dry, blackened stains. From these small areas, 143 cyanobacterial strains were established. The strains were divided into five morphotypes, including unicells, unicells with baeocytes, non-branching filaments, false-branching filaments, and heterocystous strains. From the strains, 105 partial 16S rRNA gene sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A total 12 terrestrial cyanobacterial strains from our culture collections were analyzed for the taxonomic identification of Nodosilinea species. The strains were previously isolated from surfaces of building walls, stairs, monuments, or roadside walls within Ryukyus campus (Nguyen et al 2017). All strains were maintained using BG-11 with pH 7.4, and kept under 14 : 10 (L : D) cycle using light intensity of approximately 40 μE m -2 s -1 at 25 ± 1°C.…”
Section: Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total 12 terrestrial cyanobacterial strains from our culture collections were analyzed for the taxonomic identification of Nodosilinea species. The strains were previously isolated from surfaces of building walls, stairs, monuments, or roadside walls within Ryukyus campus (Nguyen et al 2017). All strains were maintained using BG-11 with pH 7.4, and kept under 14 : 10 (L : D) cycle using light intensity of approximately 40 μE m -2 s -1 at 25 ± 1°C.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Traditional identification, solely based on morphology without considering genetic differences has led to taxonomic confusion because of the similarity in morphological characteristics among different taxa (Komárek 2018). It has been reported that the morphological classification does not accurately correspond to the actual evolutionary history however, the specific status of many strains is still undescribed (Nguyen et al 2017). Based on this information, we conducted more detailed identification for the undescribed cyanobacterial species from Nishihara campus of University of the Ryukyus.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with relatively low seasonality and high humidity, this may enable many species to coexistence (Mittelbach et al 2007). For example, subaerial microalgae have higher diversity in tropical/subtropical, subaerial habitats compared to temperate ecosystems (Eldridge 2001;Ortega-Morales et al 2006;Neustupa & Škaloud 2008;Keshari & Adhikary 2014;Sherwood et al 2015;Nguyen et al 2017). Moreover, cyanobacteria were found to be the second most abundant group of algae in these habitats, particularly in open spaces with higher light intensities (Neustupa & Škaloud 2008).…”
Section: Modern Polyphasic Studiesmentioning
confidence: 99%
“…They are also important members of symbiotic relationships with lichens, plants, and other phototrophs (e.g., Rai et al 2002;Usher et al 2007;Villanueva et al 2019). Not merely relegated to aquatic habitats, cyanobacteria are also common terrestrial pioneers and form the basis of cryptogamic crusts (Johansen 1993;Büdel et al 2002;Nguyen et al 2017). Cyanobacteria are also important global ecosystem level engineers and their total biomass is estimated at ca.…”
Section: Introductionmentioning
confidence: 99%